Let's speak Indonesian ayo berbahasa Indonesia - Rafferty, Ellen; Barnard, Erlin; Suharni, Lucy (Singapore NUS Press, 2014)
Let's Speak Indonesian (Ayo Berbahasa Indonesia) provides beginning and intermediate learners with an introduction to conversational Indonesian. Using a relaxed variety of standard Indonesian spoken among educated native speakers, it offers fifteen thematically-based chapters in two volumes that are rich with photographs, illustrations, and cultural explanations -- Provided by publisher.
Originally published in 2012 by University of Hawai'i Press.
Text in English and Indonesian.
Keywords: Indonesian language -- Spoken Indonesian -- Textbooks for foreign speakers -- English